2013
DOI: 10.1371/journal.pone.0064729
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin, Cardiovascular Disease and All-Cause Mortality in Patients with Type 2 Diabetes

Abstract: BackgroundHigh serum resistin has been associated with increased risk of cardiovascular disease in the general population, Only sparse and conflicting results, limited to Asian individuals, have been reported, so far, in type 2 diabetes. We studied the role of serum resistin on coronary artery disease, major cardiovascular events and all-cause mortality in type 2 diabetes.MethodsWe tested the association of circulating resistin concentrations with coronary artery disease, major cardiovascular events (cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 41 publications
7
68
0
6
Order By: Relevance
“…Human resistin, however, is not only an adipokine leading to insulin resistance, but also an inflammatory mediator. Recent studies showed that resistin is an inflammatory marker for the development of atherosclerosis in diabetic patients [7]. These findings strongly suggested that resistin may be one of the linkages between type 2 DM and chronic inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…Human resistin, however, is not only an adipokine leading to insulin resistance, but also an inflammatory mediator. Recent studies showed that resistin is an inflammatory marker for the development of atherosclerosis in diabetic patients [7]. These findings strongly suggested that resistin may be one of the linkages between type 2 DM and chronic inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…За счет ремоделирования сердце имеет возможность поддерживать внешнюю ра-ботоспособность на клинически приемлемом уровне [6]. Ремоделирование затрагивает основные механизмы функционирования миокарда, в том числе и кардио-миоцит-фибробластые связи, регулирующие обмен со-единительных белков сердечной мышцы.…”
Section: Discussionunclassified
“…In contrast, Erer et al showed the association of high baseline resistin levels with an increased risk of MACE and resistin was found to be an independent risk factor for predicting MACE in patients with AMI [19]. In a study, systemic review and meta-analysis, Fontana et al analyzed data from Gargano Heart Study (GHS) which was prospective in nature, to investigate the association between resistin and both all cause and cardiovascular (CV) mortality risk [20] [21]. There was 7 studies (n = 4016; 961 events) for all-cause mortality and 6 studies (n = 4187; 961 events) for CV mortality in this meta-analysis.…”
Section: U Y Sinan Et Al World Journal Of Cardiovascular Diseasesmentioning
confidence: 99%